DETERMINATION OF BRAIN ELECTRICAL SIGNAL ACQUISITION TECHNIQUESUSING TELEMETRY EQUIPMENT - Silva, Ana C. S.; Onody, Guilherme A.; Moraes, André L.; Arce, Aldo I. C.; SAVASTANO JR, Holmer; Costa, Ernane J. X. (Revista Brasileira de Engenharia de Biossistemas, 2007)
The experiments were carried out in Pirassununga, at São Paulo state, two females Dutch race bovines were used (2.5 years old). To determine the ideal techniques forgrown bovines’ brain electrical activity acquisition, using telemetric equipment, tests ofelectrode and acquisition equipement placement and fixation were made. After determination of electrode placement and fixation signal was sampled at 100 Hz and because animal’s movements acquired data presented a lot of artifacts, before spectral density calculus artifact-free stretches of 5 s duration were selected. Frequencies werein agreement with literature results despite authors used to work with needle electrodes and calves. Results indicated that it is possible to acquire EEG signal from grown bovines using telemetric equipment and scalp electrodes.